The quest for sustainable employment: Challenges faced by young people during the job‐search process. Issue 1 (7th March 2019) - Moore, Katherine
Abstract: Young people who are unable to find and sustain employment are at risk for long‐term social and economic exclusion. Active labour market policies (ALMPs) addressing the problem of youth unemployment have focused on building the employability skills of young job seekers to expand their employment opportunities. Yet research exploring how young people navigate the job‐search process is limited. Drawing on interviews with young Australian job seekers and their employment consultants, this article addresses the questions of how young people navigate entry into employment through the job‐search process and what challenges they face. The study revealed three common frustrations experienced by the young people during their job‐search: employers' expectations of relevant work experience in the young person's preferred occupation, being required to apply for jobs not aligned with their career aspirations, and the impact of personal factors on their ability to confidently present themselves to prospective employers. The findings highlight the need for ALMPs and employers to facilitate positive employability support mechanisms that will build a stable platform from which young people can build a trajectory towards sustainable employment to reduce long‐term youth unemployment.